2022
DOI: 10.47881/342.967x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Agriculture and Food Security in Ghana; The Way Forward

Abstract: Food production, its availability and accessibility will continue to be a key contributor to human existence. The world was hit by the COVID-19 pandemic in the year 2020 and its effect trickled to reduced production in many industries across the globe. Understanding effects of the pandemic in Ghana triggered this paper. The study took the form of a desk review where current studies across the globe on the effect of the pandemic on agriculture and food security were reviewed, after which it was supported by dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…It reflects the impact of COVID-19 on the various sections of the value chain and its actors, which invariably affects their profit earned. It was captured by [ 5 , 20 , 23 ] that COVID-19 influenced and disrupted the activities of the value chain actors. From the producers’ side these include the disruption of input accessibility, unreliable market, low or uncertain prices for farm produce and panic-harvesting to avert heavy losses.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It reflects the impact of COVID-19 on the various sections of the value chain and its actors, which invariably affects their profit earned. It was captured by [ 5 , 20 , 23 ] that COVID-19 influenced and disrupted the activities of the value chain actors. From the producers’ side these include the disruption of input accessibility, unreliable market, low or uncertain prices for farm produce and panic-harvesting to avert heavy losses.…”
Section: Methodsmentioning
confidence: 99%
“…The study further revealed that processors and retailers play a crucial role in ensuring information dissemination due to their contact with a lot of producers and consumers and other stakeholders. However, the stakeholders with the lowest number of ties are input dealers and wholesalers (4), and non-FBO farmers (5). The weak ties position them on the periphery of the network.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations